Complex solutions of trigonometric equations and The roots of the equation sin(x) = a - Muhammademinov Alijon Azizjon Ogli (Genius Journals, 2023)
This article deals with complex solutions of trigonometric equations in an undefined interval. That is, we were taught that trigonometric functions, especially equations such as Sin(x), do not have a solution if they are not in the interval [-1;1]. But in this article, the range of values of Sin(x) is [-1; 1] accepts non-interval states and we will see that they have a complex form
Keywords: Complex number; trigonometric equation; system of equations; area of values